Productive failure : writing queer transnational South Asian art histories - Patel, Alpesh Kantilal (Rethinking art's histories., 2017)
This monograph sets out to write new transnational South Asian art histories - to make visible histories of artworks that remain marginalised within the discipline of art history. However, this is done through a deliberate 'productive failure' - specifically, by not upholding the strictly genealogical approach that is regularly assumed for South Asian art histories. For instance, one chapter explores the abstract work of Cy Twombly and Natvar Bhavsar. I also examine 'whiteness', the invisible ground upon which racialized art histories often pivot, as a fraught yet productive site for writing art history. As the book progresses, art historical 'writing' includes a range of practice-led forms, such as curating exhibitions or my affective engagement with visual culture. Overall, I suggest methods for generating art history that acknowledge the complex web of factors within which art history is produced and the different forms of knowledge-production we might count as art history.